The Mechanotransduction Channel and Organic Cation Transporter Are Critical for Cisplatin Ototoxicity in Murine Hair Cells - Li, Jinan; Liu, Chang; Kaefer, Samuel; Youssef, Mariam; Zhao, Bo (Frontiers in Molecular Neuroscience, 2022)
Cisplatin is one of the most widely used chemotherapeutic drugs across the world. However, the serious ototoxic effects, leading to permanent hair cell death and hearing loss, significantly limit the utility of cisplatin. In zebrafish, the functional mechanotransduction channel is required for cisplatin ototoxicity. However, it is still unclear the extent to which the mechanotransduction channel is involved in cisplatin uptake and ototoxicity in mammalian hair cells. Herein, we show that genetically disrupting mechanotransduction in mouse partially protects hair cells from cisplatin-induced hair cell death. Using a fluorescent-dye conjugated cisplatin, we monitored cisplatin uptake in cochlear explants and found that functional mechanotransduction is required for the uptake of cisplatin in murine hair cells. In addition, cimetidine, an inhibitor of the organic cation transporter, also partially protects hair cells from cisplatin ototoxicity. Notably, the otoprotective effects of cimetidine do not require mechanotransduction. These findings suggest that both the mechanotransduction channel and the organic cation transporter are critical for cisplatin ototoxicity in murine hair cells.